A new species of Stylosanthes (Leguminosae - Papilionoideae) from the Chapada das Mesas National Park in Maranhao, Brazil - Gissi, Danilo Soares [UNESP]; Torke, Benjamin M.; Tomazello-Filho, Mario; Fortuna-Perez, Ana Paula [UNESP] (Springer, 2023)
A new species of Stylosanthes (Leguminosae - Papilionoideae) from the Chapada das Mesas National Park in Maranhao, Brazil, is described. The new species, S. acicularis, was misidentified as S. angustifolia in the SLUI herbarium. It differs from S. angustifolia especially by inflorescence shape and rostrum length. The new species closely resembles S. hippocampoides by its small capitate inflorescences, absence of a rudimentary axis beneath the flower, only one inner bracteole, loments with only one fertile article and a very short rostrum, and the absence of a marginal vein and possession of up to five secondary veins in the leaflets. However, the two species differ by stem indumentum, bristle length, leaflet shape and venation, and shape of the outer bracteole margin. A morphological description, illustrations-including X-ray imaging of the leaflet venation-and notes on the geographical distribution, habitat, and conservation status of the new species are presented.
Keywords: Fabaceae; Dalbergieae; X-ray; venation; taxonomy; forage